Confirming a Role for α9nAChRs and SK Potassium Channels in Type II Hair Cells of the Turtle Posterior Crista - Parks, Xiaorong Xu; Contini, Donatella; Jordan, Paivi M.; Holt, Joseph C. (Frontiers in Cellular Neuroscience, 2017)
In turtle posterior cristae, cholinergic vestibular efferent neurons (VENs) synapse on type II hair cells, bouton afferents innervating type II hair cells, and afferent calyces innervating type I hair cells. Electrical stimulation of VENs releases acetylcholine (ACh) at these synapses to exert diverse effects on afferent background discharge including rapid inhibition of bouton afferents and excitation of calyx-bearing afferents. Efferent-mediated inhibition is most pronounced in bouton afferents innervating type II hair cells near the torus, but becomes progressively smaller and briefer when moving longitudinally through the crista towards afferents innervating the planum. Sharp-electrode recordings have inferred that efferent-mediated inhibition of bouton afferents requires the sequential activation of alpha9-containing nicotinic ACh receptors (α9*nAChRs) and small-conductance, calcium-dependent potassium channels (SK) in type II hair cells. Gradations in the strength of efferent-mediated inhibition across the crista likely reflect variations in α9*nAChRs and/or SK activation in type II hair cells from those different regions. However, in turtle cristae, neither inference has been confirmed with direct recordings from type II hair cells. To address these gaps, we performed whole-cell, patch-clamp recordings from type II hair cells within a split-epithelial preparation of the turtle posterior crista. Here, we can easily visualize and record hair cells while maintaining their native location within the neuroepithelium. Consistent with α9nAChR/SK activation, ACh-sensitive currents in type II hair cells were inward at hyperpolarizing potentials but reversed near -90 mV to produce outward currents that typically peaked around -20 mV. ACh-sensitive currents were largest in torus hair cells but absent from hair cells near the planum. In current clamp recordings under zero-current conditions, ACh robustly hyperpolarized type II hair cells. ACh-sensitive responses were reversibly blocked by the α9*nAChR antagonists ICS, strychnine, and methyllycaconitine as well as the SK antagonists apamin and UCL1684. Intact efferent terminals in the split-epithelial preparation spontaneously released ACh that also activated α9*nAChRs/SK in type II hair cells. These release events were accelerated with high-potassium external solution and all events were blocked by strychnine, ICS, methyllycaconitine and apamin. These findings provide direct evidence that activation of α9nAChR/SK in turtle type II hair cells underlies efferent-mediated inhibition of bouton afferents.